The effect of meal frequency in a reduced-energy regimen on the gastrointestinal and appetite hormones in patients with type 2 diabetes: A randomised crossover study - Belinova, Lenka; Kahleova, Hana; Malinska, Hana; Topolcan, Ondrej; Windrichova, Jindra; Oliyarnyk, Olena; Kazdová, Ludmila; Hill, Martin; Pelikanova, Terezie (PLoS One, 2017)
BACKGROUND: Appetite and gastrointestinal hormones (GIHs) participate in energy homeostasis, feeding behavior and regulation of body weight. We demonstrated previously the superior effect of a hypocaloric diet regimen with lower meal frequency (B2) on body weight, hepatic fat content, insulin sensitivity and feelings of hunger compared to the same diet divided into six smaller meals a day (A6). Studies with isoenergetic diet regimens indicate that lower meal frequency should also have an effect on fasting and postprandial responses of GIHs. The aim of this secondary analysis was to explore the effect of two hypocaloric diet regimens on fasting levels of appetite and GIHs and on their postprandial responses after a standard meal. It was hypothesized that lower meal frequency in a reduced-energy regimen leading to greater body weight reduction and reduced hunger would be associated with decreased plasma concentrations of GIHs: gastric inhibitory peptide (GIP), glucagon-like peptide-1(GLP-1), peptide YY(PYY), pancreatic polypeptide (PP) and leptin and increased plasma concentration of ghrelin. The postprandial response of satiety hormones (GLP-1, PYY and PP) and postprandial suppression of ghrelin will be improved. METHODS: In a randomized crossover study, 54 patients suffering from type 2 diabetes (T2D) underwent both regimens. The concentrations of GLP-1, GIP, PP, PYY, amylin, leptin and ghrelin were determined using multiplex immunoanalyses. RESULTS: Fasting leptin and GIP decreased in response to both regimens with no difference between the treatments (p = 0.37 and p = 0.83, respectively). Fasting ghrelin decreased in A6 and increased in B2 (with difference between regimens p = 0.023). Fasting PP increased in B2with no significant difference between regimens (p = 0.17). Neither GLP-1 nor PYY did change in either regimen. The decrease in body weight correlated negatively with changes in fasting ghrelin (r = -0.4, p<0.043) and the postprandial reduction of ghrelin correlated positively with its fasting level (r = 0.9, p<0.001). The postprandial responses of GIHs and appetite hormones were similar after both diet regimens. CONCLUSIONS: Both hypocaloric diet regimens reduced fasting leptin and GIP and postprandial response of GIP comparably. The postprandial responses of GIHs and appetite hormones were similar after both diet regimens. Eating only breakfast and lunch increased fasting plasma ghrelin more than the same caloric restriction split into six meals. The changes in fasting ghrelin correlated negatively with the decrease in body weight. These results suggest that for type 2 diabetic patients on a hypocaloric diet, eating larger breakfast and lunch may be more efficient than six smaller meals during the day.
Keywords: dospělí; Caloric Restriction; Female; ghrelin; klinické křížové studie; Meals; Adult; výsledek terapie; ženské pohlaví; Diabetes Mellitus, Type 2; Leptin; Time Factors; časové faktory; lidé; glukagonu podobný peptid 1; peptid YY; diabetes mellitus 2. typu; Treatment Outcome; Cross-Over Studies; hlad; jídla; Middle Aged; tělesná hmotnost; leptin; Male; Aged; žaludeční inhibiční polypeptid; Gastric Inhibitory Polypeptide; Insulin Resistance; Pancreatic Polypeptide; inzulinová rezistence; Ghrelin; pankreatický polypeptid; Body Weight; Glucagon-Like Peptide 1; lidé středního věku; senioři; mužské pohlaví; Peptide YY; Hunger; kalorická restrikce; Humans